Early experience of laparoscopic and robotic hybrid pancreaticoduodenectomy. Issue 3 (9th March 2017) - Kim, Hongbeom; Kim, Jae Ri; Han, Youngmin; Kwon, Wooil; Kim, Sun‐Whe; Jang, Jin‐Young
Abstract: Background: Laparoscopic surgery and robotic surgery have their own merits and demerits. The aim of this study was to evaluate early experiences of hybrid pancreaticoduodenectomy (PD) and to identify the learning curve of robotic surgery. Methods: Sixteen patients underwent hybrid PD from August 2015 to February 2016. The outcomes were compared with those of an open PD group by the same operator during the same period. The resection time and anastomosis time were analyzed. Results: Six patients in the hybrid PD group developed complications. The postoperative hospital stay in the hybrid surgery group was significantly shorter than the open PD group (10.9 ± 3.2 vs 16.9 ± 8.8 days). The total operative time of hybrid surgery was significantly longer than that of open surgery (414.7 ± 47.0 vs 266.0 ± 51.1 minutes). In hybrid surgery, the actual operation time reduced with experience, particularly anastomosis time. Conclusion: Hybrid PD is feasible and safe. The learning curve of hybrid surgery, particularly robotic anastomosis, is relatively short.